2012
DOI: 10.1111/j.1365-2044.2011.06999.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of malleable stylet and reusable and disposable bougies by paramedics in a simulated difficult intubation

Abstract: SummaryIn a randomised crossover study, 60 ambulance paramedics attempted tracheal intubation of a manikin model of a Cormack and Lehane grade 3 ⁄ 4 view using a Portex stylet, Portex and Frova single-use bougies, and a Portex reusable bougie. Tracheal intubation within 30 s was achieved by 34 ⁄ 60 (57%) using the stylet, 18 ⁄ 60 (30%) using a Portex single-use bougie, 16 ⁄ 60 (27%) using a Frova single-use bougie and 5 ⁄ 60 (8%) using a Portex reusable bougie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Sharma outlined the limitations of GlideScope "intubation" as opposed to "laryngoscopy", suggesting that the two should be considered separately [19]. Previous comparative manikin studies include laryngoscopy time, measuring the time the blade enters the mouth until the ETT is fully inserted [12,16,20]. By excluding laryngoscopy and providing a static, constant view of the larynx, we provided the same view for each participant in both arms of the crossover study.…”
Section: Limitationsmentioning
confidence: 99%
“…Sharma outlined the limitations of GlideScope "intubation" as opposed to "laryngoscopy", suggesting that the two should be considered separately [19]. Previous comparative manikin studies include laryngoscopy time, measuring the time the blade enters the mouth until the ETT is fully inserted [12,16,20]. By excluding laryngoscopy and providing a static, constant view of the larynx, we provided the same view for each participant in both arms of the crossover study.…”
Section: Limitationsmentioning
confidence: 99%
“…It is recommended that when speed of endotracheal intubation is important (as in a patient undergoing cardiopulmonary resuscitation), an endotracheal tube should always be equipped with a stylet. In a randomized crossover study, Gregory et al (4) found that when the endotracheal intubation was performed by ambulance paramedics in a manikin of Cormack-Lehane grade 3 or 4 laryngoscopic view, the malleable stylet facilitated the highest intubation success rate with the shortest breathto-breath interval when compared with the Frova single-use bougie, Portex reusable bougie, and Portex single-use bougie.…”
Section: Comparing Performance Of Video and Direct Laryngoscopes For mentioning
confidence: 97%
“…The nine remaining studies had their reference lists screened and a further four studies were identified and included. A total of 13 studies were therefore included in our qualitative synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Of these studies, 10 were included in our quantitative synthesis [14,15,[19][20][21][22][23][24][25][26].…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 13 studies were therefore included in our qualitative synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Of these studies, 10 were included in our quantitative synthesis [14,15,[19][20][21][22][23][24][25][26]. This study selection process has been summarised in a PRISMA flow chart (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation